PTEN, Longevity and Age-related Diseases - Tait, I; Li, Y; Lu, J (My University, 2013)
Since the discovery of PTEN, this protein has been shown to be an effective suppressor of cancer and a contributor to longevity. This report will review, in depth, the associations between PTEN and other molecules, its mutations and regulations in order to present how PTEN can be used to increase longevity. This report will collect recent research of PTEN and use this to discuss PTEN’s role in caloric restriction, antioxidative defense of DNA-damage and the role it plays in suppressing tumors. The report will also discuss that variety of ways that PTEN can be compromised, through mutations, complete loss of alleles and its main antagonist, the PI3K/AKT pathway.
Keywords: PTEN; Aging; Longevity; Caloric; Restriction; DNA; Damage; Gene